The Effect of Teaching Method and Lecture Program on Students’ Satisfaction Rates and Academic Achievement - Tomo Djudin (STKIP Singkawang, 2018)
This research examined the effect of teaching method and lecture program on student satisfaction rate and academic achievement of physics education department of Education and Teacher Training (FKIP) of Tanjungpura University, Pontianak. The descriptive method with the causal-comparative study was employed in this research. The sample was (232) respondents of fifth semester in academic year 2016/2017 which drawn by using unproportioned stratified random sampling technique. A questionnaire of lecturer academic service satisfaction was administered. Based on data analysis, the findings of this research are: (1) There is a significant difference of student's satisfaction rate with lecturers’ academic service (t = 5.455, p ‹ 0.05) and academic achievement (t = 4.149, p ‹ 0.05) in terms of lecture method and direct instruction model. The students who having received direct instruction show higher on statisfaction rate and academic achevement than who having received lecture method; (2) There is a significant main effect of the lecture program on the rate of student satisfaction (F= 30.346, p ‹ 0.05) and on students academic achievement (F= 15.646, p ‹ 0.05); (3) There is no significant interaction effect of the teaching method and lecture program on student satisfaction rate (F= 0.753, p › 0.05) and academic achievement (F= 0.326, p › 0.05). It recommends that an institution should undertake internal survey to explore student satisfaction with academic services periodically.